Nothospecies ×Sorbaronia fallax (Rosaceae) in the flora of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
×Sorbaronia fallax is a complex of artificially bred intergeneric hybrids. It is one of the non-traditional fruit crops. Fruits of the nothospecies are used in as food and medicinal raw materials. ×Sorbaronia fallax is sporadically grown in orchards, forest crops, forest belts used in landscaping. In many contries, e.g. United Kingdom, Norway, Sweden, Finland, Belgium, Netherlands, Czech Republic, Estonia, Latvia, Lithuania, Poland, Belarus, some regions of Russian Federation, and the United States (Connecticut), ×S. fallax belongs to invasive species. During our field trips in 2018 and 2020, we noted several cases of occurrence this nothospecies outside of culture. The aim was to generalize information about the spontaneous spread of ×S. fallax outside the cultivation sites and outline its secondary area in Ukraine. We discuss the problem of taxonomy and nomenclature of "chokeberry", which is common in Ukraine and is apomictic microspecies. In our opinion, it would be appropriate to use the name ×Sorbaronia mitschurinii for this nothotaxon, but this would contradict the International Code of Nomenclature for algae, fungi, and plants. The central part of the publication is devoted to analyzing available sources on the cultivation and spontaneous distribution of ×S. fallax in Ukraine. This nothotaxon now spontaneously grows in Lviv, Ivano-Frankivsk, Volyn, Rivne, Zhytomyr, Kyiv, and Sumy regions, as well as in the vicinity of Kyiv. It spreads spontaneously on forest frinnges, on glades, along forest roads, on pastures, meadows, swamps, and peatlands. ×Sorbaronia fallax is eukenophyte and ergasiophyte. Local spontaneous populations of ×S. fallax are primarily small, but some of them consist a few dozen to several hundred individuals. We assumed that there is reason to consider ×S. fallax as a potentially invasive nothospecies in the northern and western regions of Ukraine. In the appendices, we provide both lists of ×S. fallax location in culture and list its records outside culture.
Keywords: black chokeberry, Aronia, Sorbus, invasive species, expansion.